2019
DOI: 10.1158/1538-7445.sabcs18-p2-08-37
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P2-08-37: The prognostic impact of synaptojanin 2 expression in estrogen receptor α-positive breast cancer patients

Abstract: Background: Synaptojanin 2 (SYNJ2) was reported to be a druggable mediator of metastasis. It is overexpressed and amplified in breast cancer, particularly estrogen receptor α (ERα)-positive breast cancer. SYNJ2 was also shown to promote cell migration and invasion in breast cancer xenograft cultures and lung metastasis in mice. Here, we investigated SYNJ2 mRNA expression in breast cancer patients during long-term follow-up. Materials and methods: A total of 434 invasive breast cancer tissues wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…RAI2 has been proven to suppress early hematogenous dissemination of breast cancer and indicate favorable prognosis by analyzing hundreds of breast cancer patient samples. However, these results need further validation with more patient samples (10,12). Our results showed that high RAI2 expression could be regarded as an independent and favorable prognostic biomarker for BRCA patients, which predicts tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…RAI2 has been proven to suppress early hematogenous dissemination of breast cancer and indicate favorable prognosis by analyzing hundreds of breast cancer patient samples. However, these results need further validation with more patient samples (10,12). Our results showed that high RAI2 expression could be regarded as an independent and favorable prognostic biomarker for BRCA patients, which predicts tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, RAI2 inhibited AKT signaling to suppress CRC progression, and methylated RAI2 indicated poor prognosis in CRC (11). Some studies used invasive breast cancer tissues to indicate that lower RAI2 mRNA and protein were independent risk factors for lower shorter disease-free survival (DFS), and breast-cancer-specific survival (BCSS) (12). However, there are not sufficient studies to explain the biological function of RAI2 in BRCA.…”
Section: Introductionmentioning
confidence: 99%